tính: ( a+b+c) . ( a-b+c)
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
\(a,\frac{1}{a}+\frac{1}{b}+\frac{1}{c}=0=>\frac{ab+bc+ac}{abc}=0=>ab+bc+ac=0.abc=0\)
Mà \(a+b+c=1=>\left(a+b+c\right)^2=1=>a^2+b^2+c^2+2ab+2bc+2ac=1\)
\(=>a^2+b^2+c^2+2\left(ab+bc+ac\right)=1=>a^2+b^2+c^2=1-0=1\) (vì ab+bc+ac=0)
\(b,S=\frac{a}{b+c}+\frac{b}{a+c}+\frac{c}{a+b}=\left(\frac{a}{b+c}+1\right)+\left(\frac{b}{a+c}+1\right)+\left(\frac{c}{a+b}+1\right)-3\)
\(=\frac{a+b+c}{b+c}+\frac{a+b+c}{a+c}+\frac{a+b+c}{a+b}-3=\left(a+b+c\right).\left(\frac{1}{a+b}+\frac{1}{b+c}+\frac{1}{a+c}\right)-3\)
\(=2014.\frac{1}{2014}-3=1-3=-2\)
Vậy.....................
a) \(A+B=-12x^2y^4-6x^2y^4=-18x^2y^4\)
\(A+C=-12x^2y^4+9x^2y^4=-3x^2y^4\)
\(B+C=-6x^2y^4+9x^2y^4=3x^2y^4\)
a) A+B=−12x2y4−6x2y4=−18x2y4A+B=−12x2y4−6x2y4=−18x2y4
A+C=−12x2y4+9x2y4=−3x2y4A+C=−12x2y4+9x2y4=−3x2y4
B+C=−6x2y4+9x2y4=3x2y
Hẳn là khai triển...
Ta có: \(\left(a+b+c\right)\left(a-b+c\right)\)
\(=\left[\left(a+c\right)+b\right]\left[\left(a+c\right)-b\right]\)
\(=\left(a+c\right)^2-b^2\)
\(=a^2+2ac+c^2-b^2\)